Implementation of Clinical Pathways as A Strategy To Address Pending BPJS Claims - ingrid susanti; Dasrun Hidayat; Kahar Mulyani (Finance and Business Management Journal, 2026)
Pending BPJS Health claims are a recurring problem that affects hospital cash flow, cost efficiency, and service quality. At Rama Hadi Hospital Purwakarta, the average pending claim rate in 2025 reached 12.5% for outpatient services and 20% for inpatient services, with monthly fluctuations that did not indicate sustained improvement. This study aimed to analyze the profile of pending claims, strategies for improving the quality of medical documentation, the implementation of clinical pathways, the involvement of the casemix team, their impact on cost efficiency and service quality, and the formulation of effective management strategies. A descriptive qualitative approach was used, involving seven purposively selected participants consisting of an internal verifier, case manager, claims officer, coder, hospital director, general practitioner, and specialist physician. Data were collected through in-depth interviews, observation, and document review, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that pending claims were mainly caused by incomplete medical summaries, operative reports, and supporting examination results. Clinical pathways contributed to reducing variations in care and the risk of pending claims, although their implementation remained constrained by patient comorbidities and differences in perception among specialist physicians. The casemix team played an important role in ensuring coding accuracy based on ICD-10 and INA-CBG, but continued to face challenges related to documentation compliance and differences in interpretation with BPJS verifiers. High pending claim rates disrupted cash flow and potentially affected the continuity of service quality. This study concluded that reducing pending claims requires an integrated strategy involving stronger EMR-based documentation, improved compliance with clinical pathways, optimization of the casemix team, continuous monitoring, and the use of digital technology.